2002
DOI: 10.1074/jbc.c200171200
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated Protein Kinase Suppresses Protein Synthesis in Rat Skeletal Muscle through Down-regulated Mammalian Target of Rapamycin (mTOR) Signaling

Abstract: AMP-activated protein kinase (AMPK) is viewed as an energy sensor that acts to modulate glucose uptake and fatty acid oxidation in skeletal muscle. Given that protein synthesis is a high energy-consuming process, it may be transiently depressed during cellular energy stress. Thus, the intent of this investigation was to examine whether AMPK activation modulates the translational control of protein synthesis in skeletal muscle. Injections of 5-aminoimidazole-4-carboxamide 1-␤-D-ribonucleoside (AICAR) were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
601
2
15

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 743 publications
(645 citation statements)
references
References 30 publications
27
601
2
15
Order By: Relevance
“…The connection to mTOR became apparent when it was found that 5 0 -aminoimidazole-4-carboxamide riboside (ALCAR), a synthetic AMP analog, could activate AMPK, leading to decreased S6K Thr389 phosphorylation (Bolster et al, 2002) and that AMPK phosphorylated TSC2 on at least two residues leading to an enhanced activity of the latter (Inoki et al, 2003b). AMPK via TSC2 downregulates TOR/S6K activity in response to energy deprivation (Inoki et al, 2003b).…”
Section: Energy and Nutrient Availabilitymentioning
confidence: 99%
“…The connection to mTOR became apparent when it was found that 5 0 -aminoimidazole-4-carboxamide riboside (ALCAR), a synthetic AMP analog, could activate AMPK, leading to decreased S6K Thr389 phosphorylation (Bolster et al, 2002) and that AMPK phosphorylated TSC2 on at least two residues leading to an enhanced activity of the latter (Inoki et al, 2003b). AMPK via TSC2 downregulates TOR/S6K activity in response to energy deprivation (Inoki et al, 2003b).…”
Section: Energy and Nutrient Availabilitymentioning
confidence: 99%
“…A second generally accepted consequence is the reduction of ATP synthesis [26,79]; and ATP depletion is known to activate the AMPK response [80] as a protective mechanism. Both amino acid depletion and AMPK activation can result in inhibition of mTOR [51,81] which in turn inhibits translation, protein synthesis, and cellular growth, and induces autophagy ( Figure 6). …”
Section: Amino Acid Deprivation Induces Autophagymentioning
confidence: 99%
“…Additionally, AKT may also activate the MTOR pathway by the inhibition of AMPK-mediated phosphorylation of TSC2 47 and AMPK may inhibit MTOR directly by modulating its phosphorylation site. [60][61][62] Moreover, direct physical interaction between AMPK or MTOR and ULK1 (unc-51 like autophagy activating kinase 1) plays a crucial role in the regulation of mammalian autophagy. [63][64][65][66][67][68][69] Under conditions of nutrients abundance, the activated MTOR phosphorylates ULK1 and prevents its interaction with AMPK.…”
Section: Basic Conceptsmentioning
confidence: 99%